A School Intervention's Impact on Adolescents' Health-Related Knowledge and Behavior - Nagy-Pénzes, Gabriella; Vincze, Ferenc; Bíró, Éva (Frontiers in Public Health, 2022)
Background: Many factors can influence health behavior during adolescence, and the lifestyle of adolescents is associated with health behavior during adulthood. Therefore, their behavior can determine not only present, but also later health status. Objective: We aimed to develop an intervention program to improve high school students’ health behavior and to evaluate its effectiveness. Methods: We performed our study at a secondary school in a rural town in East Hungary between 2016 and 2020. Sessions about healthy lifestyles were organized regularly for the intervention group to improve students’ knowledge, to help them acquire the right skills and attitudes, and to shape their behavior accordingly. Data collection was carried out via self-administered, anonymous questionnaires (n=192; boys=49.5%; girls=50.5%; age range: 14-16). To determine the intervention-specific effect, we took into account the differences between baseline and post-intervention status, and between the intervention and control groups using individual follow-up data. We used generalized estimating equations to assess the effectiveness of our health promotion program. Results: Our health promotion program had a positive effect on the students’ health-related knowledge and health behavior in the case of unhealthy eating, moderate to vigorous physical activity, and alcohol consumption. Conclusion: Our findings suggest that school health promotion can be effective in knowledge transfer and lifestyle modification. To achieve a more positive impact on health behavior, preventive actions must use a complex approach during implementation.